Uma nação entre dois Estados: cooperação e conflito entre Taiwan e China - Pascom, Gabriel Gomes da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The present work aims to analyze the relations of cooperation and conflict, existing since 1949, between the then newly proclaimed People’s Republic of China (PRC) against the then deposed Republic of China (RC), the latter being established, in the same year, on Formosa Island (Taiwan province). With the division of the nation between two distinct political units, to remind Raymond Aron (ARON, 2002, p. 51), a regime of conflict was established, where the legitimacy of the government over all of China was claimed by both parties. However, with the enormous economic growth of the PRC, as well as its growing international projection in recent decades, a new paradigm has developed: on the one hand, Taiwan’s growing search for representation – supported by its equally thriving and its recent democratic regime – and, on the other hand, the growing impetus of the PRC to retake the “rebel province” to its area of influence – not even ruling out the use of force and the beginning of a conflict to do so. Given this scenario, the formation of a Taiwanese nation with its own identity is raised as a hypothesis, rescuing Benedict Anderson as a theoretical reference, which well delimits the concept of imagined nation. Containing, as a consequence, the main reason for not resolving the conflict between the units, at least in a peaceful or diplomatic way.

O presente trabalho visa analisar as relações de cooperação e conflito, existentes desde 1949, entre a então recém proclamada República Popular da China (RPC) frente a então deposta República da China (RC), com esta última se estabelecendo, no mesmo ano, na Ilha de Formosa (província de Taiwan). Com a divisão da nação entre duas unidades políticas distintas, para lembrar Raymond Aron (ARON, 2002, p. 51), estabeleceu-se um regime de conflito, onde a legitimidade do governo sobre toda a China era clamada por ambas as partes. Contudo, com o enorme crescimento econômico da RPC, bem como sua crescente projeção no plano internacional nas últimas décadas, desenvolve-se um novo paradigma: por um lado, a crescente busca por representação por parte de Taiwan – amparada em sua economia igualmente pujante e seu recente regime democrático – e, por outro, o crescente ímpeto da RPC em retomar a “província rebelde” para sua área de influência – não descartando, inclusive, o uso da força e o início de um conflito para tal. Dado tal cenário, levanta-se como hipótese a formação de uma nação taiwanesa com identidade própria, resgatando enquanto referencial teórico Benedict Anderson, que bem delimita o conceito de nação imaginada. Contendo, como consequência, a razão maior à não resolução do conflito entre as unidades, ao menos de forma pacífica ou diplomática.
A nation between two states: cooperation and conflict between Taiwan and China
Keywords: Republic of China; People's Republic of China; Conflict; Legitimacy; Nation; Identity; República Popular da China; República da China; Taiwan; Conflito; Legitimidade; Formosa; Nação; Identidade